Transient expansion of synaptically connected dendritic spines upon induction of hippocampal long-term potentiation - Lang, Cynthia (National Academy of Sciences, 2004)
Dendritic spines are small protrusions from dendritic shafts that contain the postsynaptic sites of glutamatergic synapses in the brain. Spines undergo dramatic activity-dependent structural changes that are particularly prominent during neuronal development. Although changes in spine shape or number have been proposed to contribute to forms of synaptic plasticity that underlie learning and memory, the extent to which spines remain plastic in the adult brain is unclear. We find that induction of long-term potentiation (LTP) of synaptic transmission in acute hippocampal slices of adult mice evokes a reliable, transient expansion in spines that are synaptically activated, as determined with calcium imaging. Similar to LTP, transient spine expansion requires N-methyl-d-aspartate (NMDA) receptor-mediated Ca(2+) influx and actin polymerization. Moreover, like the early phase of LTP induced by the stimulation protocol, spine expansion does not require Ca(2+) influx through L-type voltage-gated Ca(2+) channels nor does it require protein synthesis. Thus, transient spine expansion is a characteristic feature of the initial phases of plasticity at mature synapses and so may contribute to synapse remodeling important for LTP.